The Drivers of International Financial Integration and their Implications on the Nigerian Economy: An Error Correction Model Approach - Ezeaku, Hillary Chijindu; Anyalechi, Kenneth Chikezie; Onwumere, Josaphat. U.J.; Okereke, E. J. (International Journal of Economics and Financial Issues, 2018)
This study examined the determinants of international financial integration (IFI) and how they impact on the Nigerian economy over the period 1986-2015. The error correction model was employed to regress the key determinants of IFI against GDP growth, and to ascertain the speed of adjustment. The results showed that financial market capitalisation and trade openness both have negative and insignificant influence on economic growth. The real effective exchange rate has positive but insignificant effect on economic growth while inflation exerted positive and significant impact on the economy. The Engel and Granger cointegration test result shows evidence of long-run association between economic growth and the independent variables. The dynamic estimate provided evidence of long-run causality running from IFI determinants to economic growth. The coefficient of the error correction term indicates that the system corrects disequilibrium in the previous period at the speed of 81.43% annually to get at the steady state. Keywords: Financial Integration, market capitalization, Openness, Growth, Cointegration JEL Classifications: F4, F43, G1 DOI: https://doi.org/10.32479/ijefi.7189